METAFUNGSI BAHASA DALAM CERITA AMASEIWI OLOKOLOQ’E: SEBUAH TINJAUAN LINGUISTIK SISTEMIK FUNGSIONAL - NFN Darmawati M.R. (Multilingual, 2013)
Language theories had variation which is based on the languages phenomenon. Systemic Functional  Grammar (SFG) for example, analyzing language metafunction in relation to language as social semiotic. This paper aims to examine language metafunction,using Buginesse folklore, 'Amaseiwi Olokoloq'e as the object.It was found that the dominant process in Amaseiwi Olokoloq'e is the material process, occurring in 19 clauses in the text, followed by 10 relational process clauses. Meanwhile, existential process occurs in six clauses, the verbal and behavioral actor only occur once. In other words, the verbal and behavioral processes are rarely found in this text. Furthermore, in this text, the process generally precedes the participants. The position of the participants, especially in the material(actor) and behavioral processes, are not always in the initial. It could be in the middle, even at the end of the clause. By using SFG perspective, difficulties encountered in analyzing the language syntax of Buginesse, in terms of providing an assessment of the klitika could be resolved. From the functional point of view, clitic can stand on its own, making it easier to analyze the text which is sometimes unusual (marked) but acceptable in the speakers context.